Perspective of Breeders and Farmers towards Participatory Plant Breeding Programme in Punjab - Faisal, Hassamuddin; Kaur, Manmeet; Anand, Anupam (Indian Journal of Extension Education, 2020)
Participatory Plant Breeding (PPB) is based on the idea that farmers as well as professional plant breeders have important knowledge and skills that could complement one another. PPB involves breeders/researchers, farmers, extension personnel, agro-industry and rural co-operatives in plant breeding research. The study was conducted in Punjab Agricultural University, Ludhiana and its research stations in different districts. The study comprised of two kinds of respondents viz. Breeders and Farmers. The total sample size was of 100, 50 breeders and 50 farmers who were randomly selected for seeking their perspective towards Participatory Plant Breeding in Punjab. The findings revealed that all the farmers were found to be unaware about the PPB while all the breeders were found to be aware about the PPB. A little less than two-third of the farmers agreed that PPB will be the best kind of breeding suitable under Punjab conditions while more than half of the breeders preferred the conventional breeding in the state. More than two-third of the farmers and a little more than half of the breeders perceived that collaborative form of participation to be best suited under PPB.
Keywords: Awareness; Breeders; Farmers; Form; Participatory plant breeding